ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATERI FUNGSI BERDASARKAN KRITERIA WATSON DITINJAU DARI PERBEDAAN GENDER SISWA SMP KELAS VIII - Saputri, Risma Rintias; Sugiarti, Titik; Murtikusuma, Randi Pratama; Trapsilasiwi, Dinawati; Yudianto, Erfan (Department of Mathematics Education , University of Jember, 2018)
Abstract. The purpose of this research is to analyze student’s errors based on Watson's criteria reviewed from gender. From the results, it can be known the types of student errors, the percentage, and the causes of student’s errors that occur. The research is descriptive qualitative. Data collection was done by test and interview. The test are given to the students to find out the types of errors that occur when they complete it. The interview with subjects is done to find out the reason why they did error in completing the test. Subject in this research are 10 students in class VIII C of Junior High School 8 Jember. Five male students and female students. Based on the result of this research, the male students are disposed to do an error omitted data with 13,33%, 13,33% response level conflict, and 16,67% above other. The female students are disposed to do an error omitted conclusion with 24,14%. Keywords: error analysis, Watson’s criteria, function, gender